State downsizing as a determinant of infant mortality and achievement of Millennium Development Goal 4 (2009)
ABSTRACT: The aim of this study was to evaluate the worldwide effect of state downsizing policies on achievement of U.N. Millennium Development Goal 4 (MDG4) on infant mortality rates. In an ecological retrospective cohort study of 161 countries, from 1978 to 2002, the authors analyzed changes in government consumption (GC) as determining exposure to achievement of MDG4. Descriptive methods and a multiple logistic regression were applied to adjust for changes in gross domestic product, level of democracy, and income inequality. Excess infant mortality in the exposed countries, attributable to reductions in GC, was estimated. Fifty countries were found to have reduced GC, and 111 had increased GC. The gap in infant mortality rate between these groups of countries doubled in the study period. Non-achievement of MDG4 was associated with reductions in GC and increases in income inequality. The excess infant mortality attributable to GC reductions in the exposed countries from 1990 to 2002 was 4,473,348 deaths. The probability of achieving MDG4 seems to be seriously compromised for many countries because of reduced public sector expenditure during the last 25 years of the 20th century, in response to World Bank/International Monetary Fund Washington Consensus policies. This seeming contradiction between the goals of different U.N. branches may be undermining achievement of MDG4 and should be taken into account when developing future global governance policy.